Sodium ferrous citrate and 5‐aminolevulinic acid improve type 2 diabetes by maintaining muscle and mitochondrial health. Issue 4 (23rd February 2023) - Kitamura, Naho; Zhang, Shiyang; Morel, Jean‐David; Nagano, Utana; Taworntawat, Tanon; Hosoda, Shotaro; Nakamura, Anna; Ogawa, Yoko; Benegiamo, Giorgia; Auwerx, Johan; Tsubota, Kazuo; Yokoyama, Yoko; et al.
Abstract: Objective: Improving mitochondrial function is a promising strategy for intervention in type 2 diabetes mellitus. This study investigated the preventive effects of sodium ferrous citrate (SFC) and 5‐aminolevulinic acid phosphate (ALA) on several metabolic dysfunctions associated with obesity because they have been shown to alleviate abnormal glucose metabolism in humans. Methods: Six‐week‐old male C57BL/6J mice were fed with a normal diet, a high‐fat diet, or a high‐fat diet supplemented with SFC and ALA for 15 weeks. Results: The simultaneous supplementation of SFC + ALA to high‐fat diet‐fed mice prevented loss of muscle mass, improved muscle strength, and reduced obesity and insulin resistance. SFC + ALA prevented abnormalities in mitochondrial morphology and reverted the diet effect on the skeletal muscle transcriptome, including the expression of glucose uptake and mitochondrial oxidative phosphorylation‐related genes. In addition, SFC + ALA prevented the decline in mitochondrial DNA copy number by enhancing mitochondrial DNA maintenance and antioxidant transcription activity, both of which are impaired in high‐fat diet‐fed mice during long‐term fasting. Conclusions: These findings suggest that SFC + ALA supplementation exerts its preventive effects in type 2 diabetes mellitus via improved skeletal muscle and mitochondrial health, further validating its application as a promising strategy for the prevention of obesity‐induced metabolic disorders.